MANAJEMEN PENDIDIKAN KELUARGA DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI KELURAHAN PASAR MUARA SIPONGI - Heru Siregar; Abdusima Nasution; Erna Ikawati (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This research is motivated by the importance of family education management in supporting children's educational success, particularly in the Pasar Muara Sipongi Village, Muara Sipongi District, Mandailing Natal Regency. Many families in this area have not yet optimized the management of their children's education at home, as evidenced by the lack of parental involvement in their children's learning processes. The aim of this study is to analyze how the planning, organizing, implementing, and controlling of family education management occurs in this region. The method used is qualitative research, with data collection techniques including observation, in-depth interviews, and documentation from six parents with children in elementary and junior high school. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results indicate that long-term educational planning has not yet become a primary priority for families; the organization of children's learning activities is poorly structured; the implementation of education remains passive and simplistic; and the control of learning activities is more reactive than preventive. Additionally, parental involvement in evaluating their children's educational processes is still minimal. In conclusion, family education management in this area needs to be improved to support the optimal development of children.